2009
DOI: 10.1111/j.1440-1681.2008.05019.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinociception Versus Serum Concentration Relationships Following Acute Administration of Intravenous Morphine in Male and Female Sprague‐dawley Rats: Differences Between the Tail Flick and Hot Plate Nociceptive Tests

Abstract: 1. Antinociception versus serum morphine concentration relationships were defined in male and female Sprague-Dawley rats administered single intravenous (i.v.) bolus doses of morphine, using the hot plate (2.1-14 mg/kg) and tail flick tests (1-8 mg/kg). 2. Serum concentrations of morphine and morphine-3-glucuronide (M3G), its major metabolite in the rat, were assayed using high-performance liquid chromatography (HPLC) with electrochemical detection. 3. Significantly higher (P < 0.05) values of peak antinocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…Less frequent, but still abundant, are the reports where a compound or condition influences the response to one of the tests but fails in the other (23)(24)(25)(26). On the other hand, studies where the two tests render opposite effects are more difficult to find.…”
Section: Discussionmentioning
confidence: 92%
“…Less frequent, but still abundant, are the reports where a compound or condition influences the response to one of the tests but fails in the other (23)(24)(25)(26). On the other hand, studies where the two tests render opposite effects are more difficult to find.…”
Section: Discussionmentioning
confidence: 92%
“…In rats, the disposition of morphine and its major biologically-active metabolite, morphine-3-glucuronide, after peripheral administration have been investigated extensively (see Smith et al, 1990; Alnouti et al, 2007; South et al, 2009). For example, South et al (2009) reported that following intravenous injection of a 10 mg/kg dose of morphine to male Sprague-Dawley rats (same dose and route of administration, and rat and gender strain as used in the present study), the blood levels of morphine (all approximate values read from the manuscript figs) peaked at 7 μΜ at 2.5 minutes (time of initial maximal effects in our study) and were at 1 μΜ at 50 minutes (time of last measurement in our study when many effects of morphine were still sustained).…”
Section: Discussionmentioning
confidence: 99%
“…For example, South et al (2009) reported that following intravenous injection of a 10 mg/kg dose of morphine to male Sprague-Dawley rats (same dose and route of administration, and rat and gender strain as used in the present study), the blood levels of morphine (all approximate values read from the manuscript figs) peaked at 7 μΜ at 2.5 minutes (time of initial maximal effects in our study) and were at 1 μΜ at 50 minutes (time of last measurement in our study when many effects of morphine were still sustained). In addition, blood concentrations of morphine-3-glucuronide were 7.5 μΜ at 2.5 minutes and 7 μΜ at 50 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences have been reported for lmorphine type opioid receptor agonist, which exhibits distinct sexual dimorphism. Sex-dependent differentiation has been reported for sensitivity to analgesic action of such a l-type opioid receptor agonist [1][2][3][4], quickness in developing tolerance and dependence [5], as well as release substance P [6]. Also, a number of investigations have confirmed the influence of morphine on the functioning of the female sexual system.…”
mentioning
confidence: 87%